Seroprevalence of Leptospira antibodies in dogs and cats from Santa Fe, a city in East-Central Argentina endemic for leptospirosis - Ricardo, Tamara (2024)
This study examines household pets as potential epidemiological links between environments contaminated with pathogenic leptospires and humans in Santa Fe, Argentina. The aims of our study were: (a) to characterize the habits and exposure to environmental sources of leptospirosis in the population of dogs and cats attending to municipal spay and neutering campaigns in Santa Fe, Argentina, (b) to assess the seroprevalence of anti-Leptospira antibodies in asymptomatic dogs and cats, (c) to evaluate factors that could increase seropositivity, and (d) to identify spatial clusters of seropositive dogs and cats in the capital city of Santa Fe.From May to November 2022, a cross-sectional serosurvey was conducted during municipal spaying/neutering campaigns. Eligible household dogs and cats were over 6 months old, apparently healthy, and not vaccinated against leptospirosis in the past 6 months. We used microagglutination test to assess anti-Leptospira antibodies using a panel of 10 reference strains. We used generalized linear mixed effects models (GLMM) to examine individual and census tract-level risk factors for seropositivity, and local Moran’s I statistic for spatial clusters.Results showed higher leptospiral antibody prevalence in dogs (18.2%) than cats (3.6%) (p = 0.002). Dogs with street access had higher seropositivity probability (OR: 3.8, 95% CI: 1.2; 11.9), and areas with chronic poverty showed an elevated risk of presenting seropositive animals (RR: 4.0, 95% CI: 1.1; 14.4). Spatial analysis didn´t reveal significant seropositivity clusters among census tracts.These findings shed light on widespread Leptospira seropositivity in pets in this endemic region. Understanding seroprevalence and risk factors can guide public and veterinary health strategies, emphasizing increased leptospirosis vaccination for dogs in vulnerable areas and promoting responsible pet care.